(untitled) (Academia Journal of Medicine, 2019)
Background: Chronic kidney disease is a silent epidemic of the 21 century. Surveys have suggestedthat as many as 16% of the adult population have CKD1. The most common, non –renal, chronic disorders in patients with ESRD are gastro intestinal disorders2. Among upper gastrointestinal lesions caused by chronic kidney disease gastritis, an esophagus is,gastric ulcers are the most prevalent lesions. Here an attempt is being made to study the upper gastro intestinal changes in chronic kidney disease and evaluate theirrelationship with the stage of CKD or GFR. Objectives: 1. To determine the prevalence of various upper gastro intestinal lesions withthe use of fibro optic endoscopy.2. To evaluate the relation between the gastro intestinal lesion with the stage ofCKD or GFR. Subjects and Methods: We conducted a cross sectional study on 50 patients ,who are diagnosed to haveChronic kidney disease and being presented to OPD and admission in NavodayaMedical College and Research Center, Raichur over a period of one year. All patientswith chronic kidney disease underwent upper gastrointestinal endoscopy wereincluded in the study. Results: Majority of the subjects belongs to age group of 31 to 40 years (26%) and least belongs to 70 to 80 years age group (6%).Out of the 50 subjects, males were 28 and females were 22.Majority of the cases in our study belonged to stage IV. 84% of the cases had upper gastrointestinal involvement on endoscopic examination in our study. Erosive gastritis (26%), either antral or fundal, was the predominant lesion found on endoscopy. Majority of the subjects having erosive gastritis, had stage IV CKD (53.8%).Out of 50 cases in our study 55% of subjects had lesions of the stomach, 26% of subjects had lesions in the duodenum, 19% of subjects had lesions in esophagus. Out of 50 subjects in our study 52% were undergoing haemodialysis and 48% of subjects were under conservative management. Majority of subjects undergoing haemodialysiswere belongs to stage V. Conclusion: Majority of the patients with chronic kidney disease have upper gastrointestinal involvement on endoscopic evaluation. Erosive gastritis is the most common upper gastrointestinal manifestation in our study. Upper gastrointestinal manifestations are predominant in stage V. Upper gastrointestinal findings are frequently observed in chronic kidney disease patients on dialysis. Early diagnosis and management can reduce mortality and morbidity and prevent fatal complication like massive upper gastrointestinal bleed.